KONSTRUKSI PEMAKNAAN IKLAN POLITIK PASANGAN AHOK-DJAROT DI TELEVISI PADA PILKADA DKI JAKARTA 2017 - Catur Priyadi (Jurnal Pustaka Komunikasi, 2018)
Political communication through advertising on the media focuses on hard selling Just as with commercial advertising, the purpose of political advertising is to persuade and motivate voters to choose a particular candidate.This study analyzes the political ads of the Ahok-DJarot couples in the Jakarta Pilgub 2017. The purpose of this research is to know semiotic analysis from political advertisement to 2 candidate and imaging on this advertisement. .The process of processing the data of this research method is done by Using semiotic analysis techniques (semiotic analysis) is to reveal the meaning in the political ads to the 3 candidates. Using the semiotic analysis approach model used is Roland Bartes's semiotics theory. Namely Connotation and Deontation. The result of this research is the meaning of every political advertisement of the candidate of cawagub candidate of DKI Jakarta 2017. Ahok-Djarot in his political advertisement means that the lifting of the people of Jakarta in the event of riots in 1998, which was raised by Muslim, a group of Groups that create riots, and divide the unity of the Unitary Republic of Indonesia.